2020
DOI: 10.19184/geosi.v5i1.13438
|View full text |Cite
|
Sign up to set email alerts
|

Water Poverty Assessment in Olorunsogo Local Government Area of Oyo State, Nigeria

Abstract: Poor access to water is often linked to poverty, human welfare, health, nutritional status, and household labour. This paper is aimed at contributing to the debate surrounding water poverty in the rural areas. Primary data obtained covering water resources, access, capacity, uses, and environment were collected using closed-ended questionnaires. Altogether, 370 household heads were sampled and were selected by systematic random sampling technique.  Multiple correlations, factor analysis and multiple regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…In this study, using A the status of water resources in different counties of Hamedan Province was evalu The study results show that the AWPI in Hamedan province is in the middle to high w poverty categories. Zarafshani and Saadvandi [44], Forouzani, Karami, Zamani Moghaddam [32], Manandhar, Pandey and Kazama [2,11,49], and Pandey, Manan and Kazama [7] also reported similar results.…”
Section: Discussionmentioning
confidence: 57%
“…In this study, using A the status of water resources in different counties of Hamedan Province was evalu The study results show that the AWPI in Hamedan province is in the middle to high w poverty categories. Zarafshani and Saadvandi [44], Forouzani, Karami, Zamani Moghaddam [32], Manandhar, Pandey and Kazama [2,11,49], and Pandey, Manan and Kazama [7] also reported similar results.…”
Section: Discussionmentioning
confidence: 57%
“…In this context, the development of policies and guidelines aimed at territorial planning to improve the water quality in hydrographic basins is necessary, providing sustainable development and the identification of land use and occupation (Asciutti et al 2019). It is crucial that studies like this be conducted since water quality can affect the health and welfare of the community in the long run (Ifabiyi et al 2020). Nunes et al (2019) showed the advantages of using total and thermotolerant coliform indicators as bacteriological markers in aquatic environments; however, their study did not correlate with the satellite images.…”
Section: Introductionmentioning
confidence: 99%